2004
DOI: 10.1097/00000542-200412000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protective Effects of Volatile Anesthetics against Renal Ischemia–Reperfusion Injury In Vivo 

Abstract: Some volatile anesthetics confer profound protection against renal ischemia-reperfusion injury compared with pentobarbital or ketamine anesthesia by attenuating inflammation. These findings may have significant clinical implications for anesthesiologists regarding the choice of volatile anesthetic agents in patients subjected to perioperative renal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
178
4
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 0 publications
9
178
4
4
Order By: Relevance
“…In addition, the protective effects against IR injury by volatile anaesthetics have been shown in the myocardium,14 brain,15 liver16 and kidney 17. These data suggest that inhaled anaesthetics may not necessarily exacerbate lung injury after CPB.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, the protective effects against IR injury by volatile anaesthetics have been shown in the myocardium,14 brain,15 liver16 and kidney 17. These data suggest that inhaled anaesthetics may not necessarily exacerbate lung injury after CPB.…”
Section: Introductionmentioning
confidence: 83%
“…These protective effects only occurred in rats treated with volatile anesthetics during both ischemia and reperfusion, and they were independent of the effects of these anesthetics on renal blood flow or blood pressure. [12] Other in vivo and in vitro studies of the same group also demonstrated that isoflurane [24] and sevoflurane [25] mediated protection from renal ischemia-reperfusion injury. On the other hand, a study [26] showed that preconditioning with sevoflurane did not protect the rat kidney from ischemia/reperfusion injury.…”
Section: Renal Variablesmentioning
confidence: 94%
“…Lee et al [12] demonstrated in rats that halogenated anesthetics (halothane, isoflurane, sevoflurane, and desflurane) reduce necrosis and inflammation and improve plasma creatinine after renal ischemia-reperfusion injury. These protective effects only occurred in rats treated with volatile anesthetics during both ischemia and reperfusion, and they were independent of the effects of these anesthetics on renal blood flow or blood pressure.…”
Section: Renal Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other anesthetics, it has been reported that KX increases the infarct size in cerebral ischemia [8] , induces hyperglycemia in fed rodents [9] , reduces TNF-α expression in rat spleen [10] and influences lipopolysaccharide-induced endotoxemia [11] . Some anesthetics have cardio-or renoprotective effects which may be relevant to designing ischemia-reperfusion protocols [12,13] . They can affect the systemic hemodynamic [14] and may induce moderate to severe tissue damage [15] .…”
Section: Introductionmentioning
confidence: 99%